Kinematic and thermal structure at the onset of high-mass star formation - Bihr, Simon; Beuther, H.; Linz, H.; Ragan, S. E.; Hennemann, M.; Tackenberg, J.; Smith, Rowan J.; Krause, O.; Henning, Th (Astronomy and astrophysics, 2015)
Context. Even though high-mass stars are crucial for understanding a diversity of processes within our galaxy and beyond, their formation and initial conditions are still poorly constrained. Aims. We want to understand the kinematic and thermal properties of young massive gas clumps prior to and at the earliest evolutionary stages of high-mass star formation. Do we find signatures of gravitational collapse? Do we find temperature gradients in the vicinity or absence of infrared emission sources? Do we find coherent velocity structures toward the center of the dense and cold gas clumps? Methods. To determine kinematics and gas temperatures, we used ammonia, because it is known to be a good tracer and thermometer of dense gas. We observed the NH3 (1, 1) and (2, 2) lines within six very young high-mass star-forming regions comprised of infrared dark clouds (IRDCs), along with ISO-selected far-infrared emission sources (ISOSS) with the Karl G. Jansky Very Large Array (VLA) and the Effelsberg 100 m Telescope. Results. The molecular line data allows us to study velocity structures, linewidths, and gas temperatures at high spatial resolution of 3−5′′, corresponding to ~0.05 pc at a typical source distance of 2.5 kpc. We find on average cold gas clumps with temperatures in the range between 10 K and 30 K. The observations do not reveal a clear correlation between infrared emission peaks and ammonia temperature peaks. Several infrared emission sources show ammonia temperature peaks up to 30 K, whereas other infrared emission sources show no enhanced kinetic gas temperature in their surrounding. We report an upper limit for the linewidth of ~1.3 km s-1, at the spectral resolution limit of our VLA observation. This indicates a relatively low level of turbulence on the scale of the observations. Velocity gradients are present in almost all regions with typical velocity differences of 1 to 2 km s-1 and gradients of 5 to 10 km s-1 pc-1. These velocity gradients are smooth in most cases, but there is one exceptional source (ISOSS23053), for which we find several velocity components with a steep velocity gradient toward the clump centers that is larger than 30 km s-1 pc-1. This steep velocity gradient is consistent with recent models of cloud collapse. Furthermore, we report a spatial correlation of ammonia and cold dust, but we also find decreasing ammonia emission close to infrared emission sources.
Gesehen am 25.05.2020